Rancang Bangun Sistem Informasi Pengelolaan Usaha Mikro, Kecil, dan Menengah dengan Pendekatan Metode Prototype Berbasis Website (Studi Kasus : Dinas Koperasi Kota Surabaya) - Nasrullah, Muhammad; Adhe Prasetya, Bagas; Abdillah, Rosyid (LPPMPP Yayasan Sejahtera Bersama Bengkulu, 2025)
The Surabaya City Cooperative Office of Small and Medium Enterprises and Trade (DINKOPDAG) has an important role in supporting the development of the UMKM sector, but the management of UMKM data which is still carried out manually causes various obstacles such as data loss, reporting delays, and hampering the development of UMKMs. The recording process that still uses paper makes the access of UMKM players to government programs hampered. To overcome these problems, this research aims to design and build a website-based UMKM management information system using the Prototype method, with an iterative and participatory approach. The system was built using the Laravel framework, MySQL database, and tested using black-box, white-box, and User Acceptance Testing methods to ensure the system functionality runs according to the needs. The results showed that the developed information system can significantly replace manual processes into digital processes. Field officers can input data in real-time without having to come to the office, UMKM players can register independently, and DINKOPDAG can monitor the development of UMKMs and intervention activities through the available dashboard. Thus, this system provides a good solution to improve the accuracy and affordability of UMKM management in Surabaya City.